PENGARUH INFORMATION QUALITY DAN TRUST TERHADAP BUYING DECISION SECARA ONLINE (Studi Kasus pada Pengguna Media Sosial Instagram Mahasiswa STMIK GICI Batam) - Rudi Yanto Batara Silalahi; Sahara Sahara (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2017)
The purpose of this research is to be able to see the influence of information quality and trust towards online buying decision case studies on student’s social media Instagram STMIK GICI Batam. This study design using quantitative methods the hypothesis by using SPSS 20 with multiple linear regression analysis.The sampling technique used is purposive sampling with the total sample of 55 students in STMIK GICI Batam. The result of this research is the quality of information have significant influence to the purchasing decision (Sig 0,002 <0,05), trust significantly influence to purchasing decision (Sig 0,003 <0,05), and quality of information and trust simultaneously influence to purchase decision (Sig 0,000 <0,05) online through social media users instagram STMIK GICI Batam students.